2018
DOI: 10.24010/soid.490780
|View full text |Cite
|
Sign up to set email alerts
|

Seyahat Acentalarında Müşterilerin Üretime Katılım Davranışının Algılanan Hizmet Çıktılarına Etkisi

Abstract: Öz Müşterilerle üretim, işletmelere yeni fikirlerle iş yapma olanağı sunarken, müşterilerin özel isteklerinin karşılanmasını sağlamaktadır. Bu durum, gerek işletmelerin sunduğu hizmet çıktılarına gerekse müşterilerin algıladığı çıktılara etki etmektedir. Bu noktadan hareketle hazırlanan araştırmanın temel amacı, seyahat acentalarında müşterilerin üretime katılım davranışının algılanan hizmet çıktılarına etkisinin belirlenmesidir. Araştırmanın verileri, seyahat acentalarından üretime katılım yoluyla kültür turu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
1
10
0
9
Order By: Relevance
“…This result is in line with the relevant literature (Flores & Vasquez-Parraga, 2015;Prebensen & Xie, 2017;Assiouras et al, 2019). However, some researchers found that the value co-creation with customers negatively affected the satisfaction (Parks et al, 1981;Etgar, 2008;Ford & Heaton, 2000;Arıca & Kozak, 2018). In this regard, this study differs from the literature.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This result is in line with the relevant literature (Flores & Vasquez-Parraga, 2015;Prebensen & Xie, 2017;Assiouras et al, 2019). However, some researchers found that the value co-creation with customers negatively affected the satisfaction (Parks et al, 1981;Etgar, 2008;Ford & Heaton, 2000;Arıca & Kozak, 2018). In this regard, this study differs from the literature.…”
Section: Discussionsupporting
confidence: 86%
“…Within this framework, the effect of the value co-creation with customers on the tourists' citizenship behavior and satisfaction was examined. When the relevant literature is examined, it is seen that the effect of the value co-creation with customers on the service outputs such as quality (Prebensen et al, 2013;Bell & Babyak, 2018), satisfaction (Groth, 2004;Flores & Vasquez-Parraga, 2015;Prebensen & Xie, 2017;Assiouras et al, 2019), and re-purchase (Fitzpatrick et al, 2013;Park & Ha, 2016;Arıca & Kozak, 2018) has been questioned. Going beyond this, in this study, a model was developed from a holistic point of view to evaluate the effect of the value co-creation with customers on the citizenship behavior and satisfaction of the tourists, which are important both during and after the experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of co-production strategy in understanding the market in the tourism sector, determining the requests of the customers that are differentiating and getting more and more difficult to predict, personalizing the services within this framework, and increasing the competitive power of the businesses has attracted the attention of the researchers to this issue. Therefore, in the literature, the functions of the co-production in the travel agencies have been considered within different frameworks in terms of supply and demand (Wang and Fesenmaier, 2004;Prebensen and Foss, 2011;Salvado et al, 2011;Wang et al, 2011;Grissemann and Stokburger-Sauer, 2012;Bertella, 2014;Schmidt-Rauch and Schwabe, 2014;Prebensen et al, 2015;Smaliukiene et al, 2015;Tseng and Chiang, 2016;Arıca and Kozak, 2018). In the researches, the effect of the customer participation in production on the provided and perceived service outputs has been frequently examined (Wang and Fesenmaier 2004;Prebensen and Foss, 2011;Salvado et al, 2011;Wanget al.2011;Grissemann and Stokburger-Sauer, 2012;Prebensen and Dahl, 2013;Tseng and Chiang 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the researches, the effect of the customer participation in production on the provided and perceived service outputs has been frequently examined (Wang and Fesenmaier 2004;Prebensen and Foss, 2011;Salvado et al, 2011;Wanget al.2011;Grissemann and Stokburger-Sauer, 2012;Prebensen and Dahl, 2013;Tseng and Chiang 2016). In the significant part of the researches, it was found that the co-production affected the service outputs in different aspects (Wang and Fesenmaier 2004;Salvado et al, 2011;Grissemann and Stokburger-Sauer, 2012;Prebensen and Dahl, 2013;Tseng and Chiang 2016;Arıca and Kozak, 2018). However, it was determined in the literature that it was not a common practice for the travel agency customers to participate in the business processes all the way through, from the production to the consumption of the product (Grissemann and Stokburger-Sauer, 2012;Tseng and Chiang, 2016).…”
Section: Introductionmentioning
confidence: 99%